Journey by train / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2023)
It was my first journey by ETS (electric train service) to KL Sentral. Everyone was rushing into the train. I intentionally purchased the window seat at B/4D for a better view of our nature. Sitting in the train, looking out of the window, I had a stress relieving view of trees, houses, the sky, clouds…It was so green that I could feel the freshness of the surrounding outside. As I was gazing out of the window, slowly my thoughts were carried away to my younger days. It was in 1986 when I was a young, small-sized, 16-year-old girl. I was travelling back home from Teluk Intan to Seberang Jaya, the place where I practically grew up. It was my first time being distant from my family, studying in a residential school, Sekolah Menengah Sains, Teluk Intan (SEMESTI).